Kesesuaian Produk Sumut Mobile Dengan Prinsip Syariah (Studi Kasus Bank Sumut Syariah KCP Marelan Raya) - Utami, Rizky Ananda; Juliati, Yenni Samri (Universitas Labuhanbatu, 2024)
In the era of technological advancement, Islamic banking has adapted by introducing technology-based services, particularly through mobile banking. Bank Sumut Syariah, as an Islamic financial institution, also offers mobile banking services to enhance customer access and convenience in transactions. However, the importance of aligning mobile banking products with Sharia principles is a primary concern, given the foundation of Islamic banking on principles of justice, sustainability, and adherence to Islamic teachings. This research aims to identify and evaluate the profit-sharing mechanisms within Bank Sumut Syariah's mobile banking and analyze its impact on business sustainability and customer satisfaction. The research was conducted at Bank Sumut Syariah's Branch Office in Marelan Raya on November 1, 2023, utilizing a descriptive qualitative research method. Data collection methods involved observing Sumut Mobile products at Bank Sumut, particularly at Bank Sumut Syariah's Branch Office in Marelan Raya, and conducting interviews with a supervisor at the branch office. The findings revealed that Bank Sumut Syariah remains part of the conventional Bank Sumut, hence its Sumut Mobile product still operates within a conventional system. Currently, there is no separate Sharia-compliant product within Bank Sumut Syariah's mobile banking as it remains integrated with the conventional system. Nonetheless, it's crucial to ensure that every feature and transaction within Bank Sumut Syariah's mobile banking aligns with Sharia principles, encompassing cost structures, profit-sharing mechanisms, and other provisions to avoid conflicting with Sharia values. Business sustainability and customer satisfaction are key considerations in developing Sharia-compliant mobile banking products. Further studies on implementing Sharia products within Bank Sumut Syariah's mobile banking are essential to offer alternatives that align with Sharia values for customers. This research emphasizes the necessity of implementing Sharia-compliant mobile banking products to meet the demands of justice, sustainability, and compliance with Islamic teachings in modern Islamic banking activities.